Public Spending and Outcomes: Does Governance Matter? - Rajkumar, Andrew Sunil; Swaroop, Vinaya (World Bank, Washington, D.C., 2013)
The authors examine the role of governance-measured by level of corruption and quality of bureaucracy-and ask how it affects the relationship between public spending and outcomes. Their main innovation is to see if differences in efficacy of public spending can be explained by quality of governance. The authors find that public health spending lowers child and infant mortality rates in countries with good governance. The results also indicate that as countries improve their governance, public spending on primary education becomes effective in increasing primary education attainment. These findings have important implications for enhancing the development effectiveness of public spending. The lessons are particularly relevant for developing countries, where public spending on education and health is relatively low, and the state of governance is often poor.